Evaluation of Genotypic Antiviral Resistance Testing as an Alternative to Phenotypic Testing in a Patient with DOCK8 Deficiency and Severe HSV-1 Disease. (23rd January 2020) - Casto, Amanda M; Stout, Sean C; Selvarangan, Rangaraj; Freeman, Alexandra F; Newell, Brandon D; Stahl, Erin D; Ahmed, Atif A; Greninger, Alexander L; Yin, Dwight E
Abstract: Antiviral resistance frequently complicates the treatment of herpes simplex virus (HSV) infections in immunocompromised patients. Here we present the case of an adolescent boy with dedicator of cytokinesis 8 (DOCK8) deficiency, who experienced recurrent infections with resistant HSV-1. We used both phenotypic and genotypic methodologies to characterize the resistance profile of HSV-1 in the patient and conclude that genotypic testing outperformed phenotypic testing. We also present the first analysis of intrahost HSV-1 evolution in an immunocompromised patient. While HSV-1 can remain static in an immunocompetent individual for decades, the virus from this patient rapidly acquired genetic changes throughout its genome. Finally, we document a likely case of transmitted resistance in HSV-1 between the patient and his brother, who also has DOCK8 deficiency. This event demonstrates that resistant HSV-1 is transmissible among immunocompromised persons. Abstract : We show that genotypic antiviral resistance testing for HSV-1 can outperform phenotypic testing, which remains the clinical standard. We also demonstrate that HSV-1 can evolve rapidly in an immunocompromised host and that resistant HSV-1 can be transmitted between immunocompromised persons.